The usage of mobile laser scanning technologies for the estimation of forestry and forest inventory indexes of the forest stands - Vytseha, R. R.; Zajączkowski, G. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Here are presented the results of the use of mobile scanning technology (using the GeoSLAM ZEB HORIZON scanner) for the evaluation of the main forestry and inventory indicators of forest stands. The diameters of stems were calculated with the use of ground scanning and resulting values were compared with the data of direct measurement of the inventory stem strengths in pine stands. Calculations were performed of forestry and inventory indicators of stands of experimental plots (calculated average diameter, average height, absolute density, stem volume stock) based on data from laser scanning and with the use of list methods of inventory. Discrepancies in different indicators were determined and analyzed.